2020
DOI: 10.3390/ijms21041307
|View full text |Cite
|
Sign up to set email alerts
|

Carboxy-Terminal Cementum Protein 1-Derived Peptide 4 (cemp1-p4) Promotes Mineralization through wnt/β-catenin Signaling in Human Oral Mucosa Stem Cells

Abstract: Human cementum protein 1 (CEMP1) is known to induce cementoblast and osteoblast differentiation and alkaline phosphatase (ALP) activity in human periodontal ligament-derived cells in vitro and promotes bone regeneration in vivo. CEMP1′s secondary structure analysis shows that it has a random-coiled structure and is considered an Intrinsic Disordered Protein (IDP). CEMP1′s short peptide sequences mimic the biological capabilities of CEMP1. However, the role and mechanisms of CEMP1′s C-terminal-derived synthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…The differentiation of osteoprogenitors is under the regulation of various signaling pathways, a number of transcriptional factors that fundamentally determine the fate of stem cells toward a “mineralizing-like” phenotype [ 56 , 57 ]. In this study, CEMP1, and CAP, as well as bone-related genes ALP, OCN, DSPP were significantly upregulated [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation of osteoprogenitors is under the regulation of various signaling pathways, a number of transcriptional factors that fundamentally determine the fate of stem cells toward a “mineralizing-like” phenotype [ 56 , 57 ]. In this study, CEMP1, and CAP, as well as bone-related genes ALP, OCN, DSPP were significantly upregulated [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced cementum thickness was noted in extracted teeth of D vs. ND subjects [ 56 ]. With reports of CEMP-1 (or its derived peptides) inducing osteogenic differentiation of gingival fibroblasts [ 57 ], oral mucosal stem cells [ 58 ] and PDL cells [ 29 ], it seems CEMP-1 functions extend beyond being a marker of cementoblastic differentiation and could be a key molecule for inducing bone and periodontal regeneration both in healthy models and under D conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study using the rat fenestration defect model demonstrated that the CEMP1‐p1 peptide induces the deposition of lamellar‐like AEFC, formation of MSC in the presence of cementocytes, and new bone formation near the cementum‐enamel junction (Hoz, López, Zeichner‐David, & Arzate, 2021). In addition to the N‐terminus‐derived peptides of CEMP1, the C‐terminus‐derived peptide of CEMP1 (CEMP‐p4) reportedly promotes mineralization through the Wnt/β‐catenin signaling pathway in human oral mucosa stem cells (Arroyo et al, 2020).…”
Section: Cementum Regeneration Using Related Proteinsmentioning
confidence: 99%